Depiction of a female figure with Ketu and Rahu - Temples of India Project Team (Jio Institute, 2024)
Broken fragment of a navagraha panel, now housed in the Government Museum, Sikar, depicting (from right to left) a female figure, Ketu, Rahu and two other planetary gods depicted akin to rishis.